The Mental Image of the Iraqi Policeman in the Anbar Province - الجابري محمد حامد عبد (ALBAHITH ALALAMI, 2015)
The study of images in the cognitive field receives considerable attention by researchers, whether in the field of media and public relations or in other humanities. Due to the great importance in shaping trends of public opinion, especially trends that individuals and the behaviors of people, institutions or ideas are determined by forming images that they hold in their minds towards these persons or institutions. Modern enterprises have realized, whether they are governmental ministries and official departments or non-governmental organizations as civil society organizations, the importance of studying the dominant image in the minds of the masses and make decisions and draw plans to configure this image as these institutions wishes.